Modelagem matemática e educação ambiental: desenvolvimento de fichas ambientais para aplicação no ensino básico - Rapelli, Osni José (2019)
This work is about the development of environment-related mathematics worksheets to give students a critical view of the world, make them search for solutions to their own communities and, in that process, understand how useful and necessary the mathematical tools are. That is the challenge that this work tries to overcome. Using Mathematical Modeling through analysis on real, serious problems concerning our environment, we introduce mathematical concepts which, through several exercises, take the students to a new thinking and rethinking about the world, perceiving information, making predictions and finding solutions to make life better for them and for their community.